2017
DOI: 10.1038/s41537-017-0014-8
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to omega-3 deprivation in a mouse model of NMDA receptor hypofunction

Abstract: Several studies have found decreased levels of ω-3 polyunsaturated fatty acids in the brain and blood of schizophrenia patients. Furthermore, dietary ω-3 supplements may improve schizophrenia symptoms and delay the onset of first-episode psychosis. We used an animal model of NMDA receptor hypofunction, NR1KD mice, to understand whether changes in glutamate neurotransmission could lead to changes in brain and serum fatty acids. We further asked whether dietary manipulations of ω-3, either depletion or supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
5
11
0
Order By: Relevance
“…In addition to their effects of dopaminergic function, n-3 PUFAs modulate glutamatergic neurotransmission, which is also aberrant in schizophrenia [198]. Most notably, in mice with reduced levels of NMDA receptors, n-3 PUFAs failed to attenuate any of the behavioral deficits resulting from NMDA receptor hypofunction; however, the NMDA receptor knock-down mice had elevated brain concentrations of n-6 PUFAs regardless of the n-3 PUFA content of their diet, and an n-3 PUFA-deficient diet increased their deficits in executive function [199]. Likewise, in an in vitro study, addition of free, but not membrane-bound, DHA to cultured rat astrocytes or rat brain membrane preparations, decreased glutamate uptake [200].…”
Section: N-3 Pufas and Schizophreniamentioning
confidence: 99%
“…In addition to their effects of dopaminergic function, n-3 PUFAs modulate glutamatergic neurotransmission, which is also aberrant in schizophrenia [198]. Most notably, in mice with reduced levels of NMDA receptors, n-3 PUFAs failed to attenuate any of the behavioral deficits resulting from NMDA receptor hypofunction; however, the NMDA receptor knock-down mice had elevated brain concentrations of n-6 PUFAs regardless of the n-3 PUFA content of their diet, and an n-3 PUFA-deficient diet increased their deficits in executive function [199]. Likewise, in an in vitro study, addition of free, but not membrane-bound, DHA to cultured rat astrocytes or rat brain membrane preparations, decreased glutamate uptake [200].…”
Section: N-3 Pufas and Schizophreniamentioning
confidence: 99%
“…GluN1KD (F1 on C57Bl/6J x 129/SvlmJ background) [ 26 ] and DATKO (C57Bl/6J background) [ 24 ] mice were used as murine models of hyperdopaminergia. All mice were tested as follows: Day 1—open-field test and Day 3—pre-pulse inhibition, as previously described [ 28 , 30 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…GluN1KD (F1 on C57Bl/6J x 129/SvlmJ background) (26) and DATKO (C57Bl/6J background) (24) mice were used as murine models of hyperdopaminergia. All mice were tested as follows: Day 1 -open field test and Day 3 -prepulse inhibition, as previously described (28,30,36,37). CNS exposure, with a brain to plasma ratio of 0.77 from a dose 10 mg/kg, i.p., (AUC 8h brain /AUC 8h plasma ) and brain concentrations of 374 ± 39 ng/mL at 30 min ( Figure S1, Table S1).…”
Section: Behavioral Testing In Murine Models Of Hyperdopaminergiamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the list of amphipathic molecules produced and released in physiological settings that could modify NMDAR channel function is potentially very long. In addition to unilateral insertion of such amphipaths into the lipid bilayer NMDAR has been shown to be affected by poly-unsaturated fatty acids (PUFAs) (Calon et al, 2005; Keleshian et al, 2014; Islam et al, 2017), which have also been reported to have significant effect on the transbilayer pressure profile and MS channel activity (Ridone et al, 2018). Consequently, we propose that asymmetric insertion of amphipathic compounds into lipid bilayers made of lipids of different poly-unsaturation can be physiologically relevant for the activity of NMDA receptors.…”
Section: Membrane Curvature As a Possible Mechanism Of Nmdar Activatimentioning
confidence: 99%